2003
DOI: 10.4141/s02-037
|View full text |Cite
|
Sign up to set email alerts
|

Soil phosphorus depletion capacity of arbuscular mycorrhizae formed by maize hybrids

Abstract: . 2003. Soil phosphorus depletion capacity of arbuscular mycorrhizae formed by maize hybrids. Can. J. Soil Sci. 83: 337-342. The ability of arbuscular mycorrhizal (AM) fungi to help their host plant absorb soil P is well known, but little attention has been paid to the effect of AM fungi on soil P depletion capacity. A greenhouse experiment was conducted to assess, under different P levels, the effects of mycorrhizae on extractable soil P and P uptake by maize hybrids with contrasting phenotypes. The experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 35 publications
(28 reference statements)
1
13
0
Order By: Relevance
“…In Experiment 2, the M ) P treatment had the highest density of external hyphae (particularly in the 10-16, 16-22 and 22-28 cm layers) compared with the NM ) P treatment. The increased soil P had an inhibitory effect on development of external hyphae, as found by others (Liu et al, 2003). The external hyphae in NM cores in Experiment 2 are likely to be from dead or saprophytic fungi (Drew, 2002;Smith et al, 2004) because there was no AM fungal colonization.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…In Experiment 2, the M ) P treatment had the highest density of external hyphae (particularly in the 10-16, 16-22 and 22-28 cm layers) compared with the NM ) P treatment. The increased soil P had an inhibitory effect on development of external hyphae, as found by others (Liu et al, 2003). The external hyphae in NM cores in Experiment 2 are likely to be from dead or saprophytic fungi (Drew, 2002;Smith et al, 2004) because there was no AM fungal colonization.…”
Section: Discussionmentioning
confidence: 74%
“…The contribution of AM hyphae to P uptake is variable. Examples include 13-20% in Zea mays (Kothari et al, 1990), more than 75% in Trifolium repens (Li et al, 1991), and up to 100% in Linum usitatissimum, Lycopersicon esculentum and Medicago truncatula (Smith et al, 2003). We hypothesize that these effects on P capture could reduce P flow-through in soil profiles.…”
Section: Introductionmentioning
confidence: 96%
“…Our previous greenhouse experiment in which an arbuscular mycorrhizal fungus was inoculated into a sterilized soil also show that the highly mycorrhizal dependent hybrid, LNS, when inoculated with AMF, can reduce soil extractable P more effectively than non-mycorrhizal plants, under low soil P conditions (Liu et al 2003).…”
Section: Discussionmentioning
confidence: 82%
“…Very few studies tested the impact of varietal diversity within a crop species on soil biological communities. However, a few studies demonstrated that crop varietal interactions with soil biota were plausible, for example, those that found higher response of local maize landraces and older varieties to mycorrhizal symbionts than from modern varieties [209][210][211].…”
Section: Of 28mentioning
confidence: 99%